THE ROLE OF FACILITATORS IN RESTORATIVE HEALTH DISPUTE RESOLUTION PROCESSES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The resolution of health disputes in Indonesia is increasingly oriented towards restorative justice mechanisms that emphasise the restoration of relationships between patients and health workers, rather than simply imposing sanctions or penalties. In this context, facilitators or mediators play a central role as neutral parties who help the parties find fair, effective, and efficient solutions through dialogue and negotiation. This study aims to examine the role of facilitators in restorative health dispute resolution based on a literature review. The results of the analysis indicate that facilitators not only function as connectors but also as information providers, educators, and mediators who maintain constructive communication and help the parties identify problems and develop alternative solutions. The existing legal framework, such as Law No. 17 of 2023 on Health, provides legitimacy and legal certainty for the role of facilitators in the mediation process. However, challenges such as differences in medical knowledge, limitations of competent facilitators, and a litigious culture still need to be addressed to achieve optimal restorative justice. With enhanced facilitator capacity and clear regulatory support, mediation is expected to become the primary solution for resolving health disputes in Indonesia.